Dampak Derajat Desentralisasi Fiskal Terhadap Kemiskinan pada Daerah di Provinsi Jawa Tengah 2020-2023 - Pramana, Anugerah Surya; Putra, Juan Pradana; Rusydiana, Milla (Politeknik Statistika STIS, 2025)
Local governments play a role as implementers of central government policies at the local level and are given the authority to carry out development through decentralization mechanisms. Decentralization provides autonomy to local governments so that they can regulate and manage their regions based on their unique social, cultural, and economic conditions. One form of decentralization is fiscal decentralization, which is the granting of rights to local governments to manage their finances independently. This study aims to evaluate the impact of fiscal decentralization, economic growth, and the human development index on poverty levels in 35 districts/cities in Central Java Province from 2020 to 2023. The analysis was conducted using the Random Effect Model (REM), selected based on the results of the Chow and Hausman tests, as it can handle the heterogeneity in panel data. The results of the study indicate that all three variables have a significant impact on poverty levels, thereby providing a foundation for poverty alleviation efforts at the local level.